Images of the East in the Short Fiction of Ivan Bunin - Juracsek, Kata (Slavica, 2020)
The article examines the images of the East in the short fiction of Ivan Bunin. With the help of the narrative model of Jan van der Eng, consisting of three basic thematic levels (action, characterization, geographical and social setting) we read and arrange the works of Bunin through the prism of postcolonial criticism. On the one hand, we will consider the arguments of traditional postcolonial studies; on the other hand, we will also take into account the postcolonial theory regarding the “second world” (Russia, Eastern and Central Europe).We start our analysis with the texts in which images of the East are only featured on one thematic level, gradually directing our attention towards the short stories in which these images determine the whole semantic structure.